Ecocriticism: Formation, Development, and Core Concepts - Ishqobilova, Xulkar Shaydullayevna (The Lingua Spectrum, 2026)
This article provides a comprehensive analysis of the formation, historical development, and fundamental concepts of ecocriticism, an interdisciplinary field that combines literary studies and environmental awareness. Ecocriticism examines how literature represents nature, ecological issues, and human-nature relationships, exploring both symbolic and realistic depictions. The study highlights methodological approaches used in ecocritical research, including close textual analysis, historical-contextual interpretation, and comparative cross-cultural perspectives. Special attention is given to how ecological consciousness is reflected in literary texts, the use of natural landscapes as symbols of social and ethical concerns, and the ways authors engage with environmental challenges. By tracing the evolution of ecocriticism from its early focus on aesthetic appreciation of nature to contemporary analyses of global ecological crises, the article underscores its significance in understanding the intersection of literature, culture, and environmental thought. This research contributes to both literary scholarship and environmental humanities, offering insights into how literature can foster ecological awareness and ethical reflection.